Facile preparation of rich β-transcrystallinity in PET fiber/iPP composites (eXPRESS Polymer Letters)
Polyethylene terephthalate (PET) fibers containing different contents of β-nucleating agent (β-NA) were meltspun from a reconstructive melt flow index rheometer at 270°C, and then blended with polypropylene (iPP). The supermolecular and phase structure of the composite were investigated by polarized optical microscopy (POM), differential scanning calorimetry (DSC), and wide-angle X-ray diffraction (WAXD). For the pure PET fiber reinforced iPP, the interfacial region was mainly composed of α-modification, though it has been demonstrated that PET fiber shows weak nucleating ability towards iPP matrix. More interestingly, when the amount of β-NA introduced into the PET fiber exceeds a critical value, the transcrystalline layer will be notably dominated by β-modification. This method to prepare β-transcrystallinity is remarkably different from those through stress or temperature control. The present results provide a facile and promising technique to prepare rich β-transcrystallinity under stress-free conditions.